Global thresholds in properties emerging from cumulative curves of marine ecosystems. (August 2019) - Libralato, Simone; Pranovi, Fabio; Zucchetta, Matteo; Anelli Monti, Marco; Link, Jason S.
Highlights: Cumulative biomass curves were analyzed across 62 Large Marine Ecosystems. Curve parameters can be used as emergent indicators of ecosystem state. Pattern discontinuities are defined as Empirical thresholds for curve parameters. Curve inflection at trophic level 3.38 and biomass at 33% are identified thresholds. Thresholds are useful for evaluating ecosystem state and management interventions. Abstract: There are several emergent properties useful as indicators of marine ecosystem status. Some of these are based on the cumulative trophic theory, which posits that biomass and production accumulate in repeatable and predictable patterns across trophic levels. These patterns result in a suite of curve parameters that can delineate when a marine ecosystem is undergoing perturbation or recovery. When looking at this suite of curve parameters, and their trajectories over time, a clear sense of perturbation, recovery, or transition can be delineated. From a set of over 3700 observations we established empirical threshold levels for the curve parameters, i.e., Trophic Level inflection point, Biomass inflection point and Steepness at 3.38 ± 0.05, 0.33 ± 0.01 and 0.50 ± 0.56, respectively. When the three parameters are examined collectively to determine whether a particular ecosystem datum was below or above each of these three thresholds, clear three-dimensional patterns emerged. First, some volumes in this 3-D space of parameters simply did not have data, and many volumes had very little. The majority of data (approximately 40%) occurred in situations with Steepness and Biomass inflection point higher than thresholds. Almost none of the ecosystems (<1%) was below all three thresholds at any point in time, a quarter of the data resulted in critical conditions for at least a couple of indicators, a little less than half of the ecosystems (52%) at any point in time seem to be quite functional from this emergent property perspective, and finally, a moderate number of ecosystems, at any point in time (22%), seem to be in some type of transition state. We assert that these emergent properties have value for delineating ecosystem state, and at the very least when the Biomass inflection point is <33% an ecosystem is understood to have been severely degraded. Using these three thresholds, and identifying whether data trajectories are crossing them or not, has strong potential to better indicate the status of marine ecosystems, trajectories thereof, and hence when management interventions are needed.